2020
DOI: 10.1111/1471-0528.16434
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac function in gestational diabetes mellitus: A longitudinal study from fetal life to infancy

Abstract: Objective To determine whether cardiac functional and structural changes in fetuses of mothers with gestational diabetes mellitus (GDM) persist in the offspring beyond the neonatal period. Design Longitudinal study. Setting Fetal Medicine Unit in a UK teaching hospital. Methods 73 women with GDM and 73 women with uncomplicated pregnancy were recruited and fetal cardiac scans were performed at 35-36 weeks' gestation. Repeat echocardiogram was performed in their offspring during infancy. Main outcome measures Fe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(33 citation statements)
references
References 28 publications
3
22
0
Order By: Relevance
“…Similar findings, including changes of fetal heart shape and biventricular diastolic disfunction at speckle tracking analysis were shown in two other studies [49,50]. Despite maternal diabetic treatment, neonatal follow-up at 6-7 months of age, showed persistent heart remodeling and impairment in diastolic and systolic ventricular function, with lower left ventricular global longitudinal systolic strain [51]. Similar to neonatal persistent changes, maternal subclinical heart dysfunction persists to at least 6 months alter delivery [33,36,37].…”
Section: Gestational Diabetes Mellitussupporting
confidence: 83%
“…Similar findings, including changes of fetal heart shape and biventricular diastolic disfunction at speckle tracking analysis were shown in two other studies [49,50]. Despite maternal diabetic treatment, neonatal follow-up at 6-7 months of age, showed persistent heart remodeling and impairment in diastolic and systolic ventricular function, with lower left ventricular global longitudinal systolic strain [51]. Similar to neonatal persistent changes, maternal subclinical heart dysfunction persists to at least 6 months alter delivery [33,36,37].…”
Section: Gestational Diabetes Mellitussupporting
confidence: 83%
“…Maternal GDM is an important factor influencing cardiac development. Studies showed that women with GDM had a higher risk of foetal congenital heart disease and foetal cardiac function and structure alterations 5,36 . However, few studies have documented the effect of GDM on child cardiac structure and function beyond infancy.…”
Section: Discussionmentioning
confidence: 99%
“…2 Maternal GDM affects intrauterine environment, increasing the risk of macrosomia, 3 congenital heart disease 4 and is associated with foetal ventricular hypertrophy. 5 Also, prenatal exposure to GDM exerts a long-term influence on offspring, leading to obesity and diabetes in childhood, which was named 'metabolic imprinting'. 6 Studies have shown that in utero programing resulting from exposure to GDM could determine cardiovascular diseases in adulthood.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Gestational diabetes can cause polyhydramnios, intrauterine infection, ketoacidosis, macrosomia, abortion, premature delivery, malformation, stillbirth, and other maternal and infant complications, which attracted clinical attention [1][2][3]. Reasonable dietary control and exercise therapy can restore blood glucose to the normal range in most patients, which needs to be combined with glucose-lowering medication if necessary.…”
Section: Introductionmentioning
confidence: 99%